Stunting and Underweight, but not Wasting are Associated with Delay in Child Development in Southwest Ethiopia - Oumer A; Girum T; Fikre Z; Bedewi J; Nuriye K; Assefa K (Dove Medical Press, 2022)
Abdu Oumer,1 Zinash Fikre,1 Tadele Girum,1 Jemal Bedewi,1 Keyredin Nuriye,2 Kenzudin Assefa1 1Department of Public Health, College of Medicine and Health Sciences, Wolkite University, Wolkite, Ethiopia; 2Department of Midwifery, College of Medicine and Health Sciences, Wolkite University, Wolkite, EthiopiaCorrespondence: Abdu OumerDepartment of Public Health, College of Medicine and Health Sciences, Wolkite University, Wolkite, EthiopiaTel +251 966365785Email Phnabu@gmail.comBackground: Stimulating care during childhood is the foundation for optimal health, learning, productivity, and social well-being throughout the life course. In addition, malnutrition is a major public health concern affecting up to half of children under-five years in Ethiopia. However, evidence on the causal contribution of malnutrition to delay in child development is poorly understood in Ethiopia.Objective: To identify the relationship between different forms of malnutrition and delay in child development among children in Southwest Ethiopia.Methods: A community-based survey was conducted among 507 randomly selected mother-child pairs in the Guraghe Zone, Southwest Ethiopia. A pretested tool and validated anthropometric measurements were used. Anthropometric indices (WFH, WFA, and HFA) were calculated in Anthros software. The data were summarized in mean, median, standard deviation, tables and charts. Bivariable and multivariable binary logistic regression (stepwise backward regression) models were fitted with nutritional status (wasting, stunting and underweight) and other potential factors associated with delay in child developmental. Adjusted odds ratios with 95% confidence intervals and p-values were reported.Results: A total of 507 mother-child (12- 59 months) pairs were included in the survey (97% response rate). The mean ASQ-3 score was 150 (± 23.4), with a minimum and maximum score of 45 and 270, respectively. A total of 149 (29.4%; 95% CI: 25.4- 33.4) children had developmental delays, where 17.2%, 16.8%, 13.4%, 10.8%, and 10.1% had delays in gross motor, communication, problem-solving, personal-social, and fine motor skills, respectively. Children of working mothers (AOR=2.9; 1.8, 4.8), preterm births (AOR=3.2; 1.4, 7.0), early initiation of complementary feeding (AOR=2.5; 1.37, 4.6), stunting (AOR=3.0; 1.9, 4.7), underweight (AOR= 2.3; 1.1, 4.7) and low dietary diversity score (AOR=3.1; 1.3, 7.5), were predictors of developmental delay.Conclusion: Child development delay is a public health concern and it is strongly associated with stunting, underweight, undiversified dietary consumption, and suboptimal infant and young child feeding practices.Keywords: developmental delay, nutritional status, associated factors, stunting, children